Migration, poverty and equality - Lykke E. Andersen (Kiel Institute for the World Economy (IfW), Poverty Reduction, Equity and Growth Network (PEGNet), 2016)
The scale of inequality around the world is almost unfathomable. The average inhabitant of Norway, Qatar and Switzerland earns more in one day than what the average inhabitant of Malawi and Burundi earns in an entire year1. If you get pregnant in Sierra Leone, you are 300 times more likely to die from pregnancy related causes than if you get pregnant in Sweden2. If you are born in Angola or the Central African Republic, you are 50 times more likely to die within your first year of life than if you are born in Singapore. Currently, about 60% of the variation in income across the globe is explained by country citizenship alone, while parental income class within the country where you were born explains another 20% (Milanovic, 2011). This means that at least 80% of the variation in income (and other income related factors) is already determined by birth, leaving less than 20% to be determined by a person's own effort, ingenuity, planning, determination, risk-taking and passion. Thus, the world is not just a place of huge inequality of outcomes, but also of huge inequality of opportunity. Inequality is becoming an increasingly concerning issue and recently 176 countries agreed that one of the Sustainable Development Goals for the next 15 years should be to "reduce inequality within and among countries." One of the specific targets associated with this goal is to "facilitate orderly, safe, regular and responsible migration and mobility of people, including through the implementation of planned and well-managed migration policies."
Keywords: 330